Using social media to advance the social rights of people with disability in China: The Beijing One Plus One Disabled Persons’ Cultural Development Centre - Kent, Michael; ellis, K.; Zhang, H.; Xu, J. (Routledge, 2016)
This book considers the specific and at this stage largely unexplored impacts of our increasing reliance on social media for people with disability through a number of international case studies.